Satellite-based Estimates of Sea Ice Volume Flux : Applications to the Fram Strait Region - Spreen, Gunnar (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2008)
The sea ice export out of the Arctic Ocean through Fram Strait into the Greenland Sea is the single largest source of freshwater in the Nordic Seas and therefore of special importance for the hydrological cycle of the North Atlantic. On its way south, the exported sea ice melts and thereby modifies the stratification of the ocean surface mixed layer, which in turn influences oceanic deep convection and water mass transformation processes in the Nordic Seas and thus impact global ocean thermohaline circulation. The lack of spatial sea ice thickness information has been one of the weaknesses for previous existing methods to determine the sea ice export. In this study a new method to obtain the sea ice volume flux exclusively from satellite measurements is presented. Previous estimates of the sea ice volume flux relayed on ice draft measurements of a single Upward Looking Sonar (ULS) in the Greenland Sea. The GLAS laser altimeter onboard the ICESat satellite launched in 2003 offers for the first time the opportunity to obtain the spatial sea ice thickness distribution up to 86°N latitude. In this study a method to determine the sea ice freeboard from ICESat altimeter data is developed and applied to nine ICESat measurement periods between 2003 and 2007. Assuming hydrostatic balance and by utilization of further satellite, in situ and climatological data these sea ice freeboard measurements are converted to sea ice thickness maps of the Fram Strait region. The satellite-based ice thickness estimates are combined with sea ice area and sea ice drift, as retrieved from AMSR-E microwave radiometer measurements at 89 GHz, to obtain the sea ice volume flux. The errors of the input quantities and the final sea ice volume flux are assessed. Using this method the spatial sea ice volume flux distribution is obtained from satellite observations for the first time. The Fram Strait sea ice volume flux is further investigated by calculating a monthly sea ice volume flux time series between January 2003 and April 2007. Summer ...